Comparative evaluation of Latanoprostene Bunod, Timolol Maleate, and latanoprost Ophthalmic Solutions to assess their safety and efficacy in lowering intraocular pressure for the management of Open-Angle Glaucoma - Wang, Yulong (Clinics (Sao Paulo), 2020)
OBJECTIVES: Timolol maleate has been reported to be a safer intraocular pressure (IOP) lowering treatment than latanoprost. The United States Food and Drug Administration approved latanoprostene bunod, a nitric oxide-donating prodrug of latanoprost, for lowering IOP. This study compared the safety and efficacy of latanoprost, latanoprostene bunod, and timolol maleate in patients with open-angle glaucoma. METHODS: Patients who received latanoprost eye drops once daily in the evening were included in the latanoprost Ophthalmic Solutions (LP) cohort (n=104). Those who received latanoprostene bunod eye drops once daily in the evening were included in the Latanoprostene Bunod (LB) cohort (n=94). Those who received timolol eye drops twice daily were included in the Timolol Maleate (TM) cohort (n=115). All treatments were administered to the affected eye(s) for 3 months. Informed Consent has been taken from each participant before the trial. RESULTS: At the end of 3 months of treatment, latanoprost, latanoprostene bunod, and timolol were all successful in reducing IOP. The LB cohort had the highest reduction in IOP, compared to the LP and TM cohorts. All treatments had some common adverse ocular effects. CONCLUSION: Latanoprostene bunod was superior to latanoprost and timolol for the treatment of open-angle glaucoma.